PROSEDUR PENGEMBANGAN BAHAN AJAR SENI MUSIK BERBASIS CTL - Ardipal - (FBS UNY, 2010)
The aim of this research and development is to analyze the procedure to develop the CTL-based music art teaching materials for students of grade 3 of elementary schools. The procedure follows Plomps development stages. The data were collected through observation, interview, questionaire and documentation. The result of the research shows that the developed teaching materials which adopted Plomps model could optimize the instructional process in music art classes in elementary schools. Keywords: procedure of development, teaching materials, music art, CTL